EFFECT OF ADVANCE ORGANIZERS ON ACADEMIC ACHIEVMENT AND RETENTION OF KINETIC THEORY OF MATTER AMONG BASIC SCIENCE AND TECHNOLOGY STUDENTS IN UYO (UNIZIK Journal of STM Education, 2025)
This study examined the effect of Advanced Organizers on academic achievement and retention of Kinetic theory of matter concepts among Basic Science and Technology students in Uyo. Four research questions and four null hypotheses gave direction to the study. The study adopted a non- randomized pre-test, post-test, control group quasi-experimental design. The population consisted of 2,010 Junior Secondary Two (JSS2) Basic Science and Technology students, while 200 students obtained through simple random sampling technique formed the sample size.  A researcherdeveloped instrument: Kinetic Theory of Matter Achievement Test (KTMAT), with a reliability co-efficient of 0.87 determined using Kuder- Richardson 21 formula, was used for data collection. The statistical tools used for analysis were the mean, standard deviation and Analysis of Covariance. The findings indicated a significant difference in the mean achievement, retention scores of students taught Kinetic Theory of Matter using Advance Organizers, and of those taught using Expository teaching method in favour of the students taught using Advance Organizers. Also, there was no significant influence of gender on the mean achievement and retention scores of the students when exposed to Advance Organizers. Consequently, it was recommended among others that, Basic Science and Technology teachers should make effective use of Advance Organizers teaching strategy in teaching Kinetic Theory of Matter concepts in Junior Secondary School.
Keywords: Advance organizers, Kinetic theory of matter, Academic achievement, Retention, Gender